Public-Private Partnership: Its Essence and Specificity - PASHINA, Lyubov L.; PASTUSHENKO, Svetlana В.; VOLKOVA, Elena A.; NENYA, Anton S.; PASHINA, Maria V. (Journal of Advanced Research in Law and Economics, 2019)
The article justifies public-private partnership from the point of view of domestic and foreign theory and practice, since the state is the initiator of the vast majority of public-private partnership projects. Therefore, there is a specific partnership between the state and business, which depends on the goals, objectives, priorities of economic policy, legislative and the regulatory and legal framework, the administrative structure and functions of government bodies, the level of development of society and legal culture. It is determined that a public-private partnership should be viewed not as a simple combination of state and business resources, but as a technology for developing economic relations that combines state business and other government corrective actions with the ability to attract private investment and private business competencies to solve social and economic problems.